2020
DOI: 10.3390/ijerph17197147
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Time of Thermotherapy for Reducing Pain, Anxiety, and Side Effects in Arteriovenous Fistula Puncture Patients: A Randomized Controlled Trial

Abstract: Chronic renal failure patients undergoing hemodialysis complain of moderate pain from repeated punctures of the arteriovenous fistula. This study examined the optimal application time of thermotherapy for reducing pain, anxiety, and side effects during arteriovenous fistula puncture. This study was conducted as a single-blinded randomized controlled trial. The participants were arteriovenous fistula puncture patients with chronic renal failure who were divided into two thermotherapy groups and one control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Also, the post-intervention reduction in pain and anxiety was not significant. This is consistent with previous findings [16,17] and can be attributed to the different properties of anxiety across individuals. In addition, the participants of this study were healthy adults aged 20-75 years, the age range was too wide, and the baseline for pain and anxiety were relatively low, so it seems that the appropriate effect could not be confirmed.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Also, the post-intervention reduction in pain and anxiety was not significant. This is consistent with previous findings [16,17] and can be attributed to the different properties of anxiety across individuals. In addition, the participants of this study were healthy adults aged 20-75 years, the age range was too wide, and the baseline for pain and anxiety were relatively low, so it seems that the appropriate effect could not be confirmed.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have included children vulnerable to pain [6e8], patients undergoing hemodialysis requiring punctures regularly [9e13], and patients with diabetes mellitus who undergo regular insulin therapy [14]. Nursing interventions that have been studied include heat and cold therapy [15,16], topical anesthetic cream [6,7,12], distraction therapy [8], aromatherapy [9], and vibration therapy [17,18], all of which have been reported to be effective in pain relief. However, topical anesthetics and aromatherapy are limited in terms of systemic absorption through the skin and the onset of action.…”
Section: Introductionmentioning
confidence: 99%
“… 39 Studies have shown that cognitive impairment due to neuropathy could predict diabetic retinopathy progression. 40 Furthermore, arteriovenous fistula/catheterization pain was one of the most severe symptoms, 41 underscoring its significance in patients with chronic renal failure and diabetes, especially those on hemodialysis. 41 Diarrhea was the most frequent symptom, corroborating findings from another study indicating a high prevalence of gastrointestinal symptoms among Chinese diabetes outpatients, with diabetes duration being a key contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Furthermore, arteriovenous fistula/catheterization pain was one of the most severe symptoms, 41 underscoring its significance in patients with chronic renal failure and diabetes, especially those on hemodialysis. 41 Diarrhea was the most frequent symptom, corroborating findings from another study indicating a high prevalence of gastrointestinal symptoms among Chinese diabetes outpatients, with diabetes duration being a key contributing factor. 42 Overall, the above-mentioned evidence suggested that healthcare providers need to pay attention to the conscious state and routine vision testing in DKD patients in the future, as well as to the possible important role of pain management in alleviating discomfort and pain.…”
Section: Discussionmentioning
confidence: 99%
“…This appeared to be due to the relaxation effect in the soft tissues after local warming. One study reported that soft tissue relaxation after heating the arteriovenous fistula site for hemodialysis in patients with chronic kidney disease reduced the pain during thick-needle insertion ( 15 ).…”
Section: Discussionmentioning
confidence: 99%